Щодо можливих механізмів участі мікробіому в індукції злоякісності - Zabolotnyi, D.; Serezhko, Yu.; Zabolotna, D.; Maliarenko, Yu.; Voroshylova, N.; Verevka, S. (PH Akademperiodyka, 2025)
The сlose coexistence of organisms of different biological species is one of the leading principles of the organization of living matter. The interaction of microbial biofilms with adjacent tissues of the host deserves special attention. The article raises controversial issues related to the possible malignant effect of microbial biofilms.